The Influence of Intellectual Intelligence, Emotional Intelligence, and Spiritual Intelligence on Employee Performance at the Central Statistical Agency of Buleleng Regency - Mahayani, Luh Sari; Rianita, Ni Made (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Human resources are an important asset and serve as the main driving factor in implementing all organizational activities, thus requiring effective management through Human Resource Management. High-quality human resources will help achieve the goals of any institution or company. This study aims to determine the effect of Intellectual, Emotional, and Spiritual Intelligence on employee performance at the Central Bureau of Statistics in Buleleng Regency. This research uses a quantitative method with data obtained from questionnaire distribution. The sample in this study consists of 33 employees of the Central Bureau of Statistics in Buleleng Regency. The data analysis technique used is multiple linear regression. The results of this study show that: (1) Intellectual Intelligence does not affect employee performance, (2) Emotional Intelligence does not affect employee performance, and (3) Spiritual Intelligence does not affect employee performance. Simultaneously, Intellectual, Emotional, and Spiritual Intelligence affect employee performance at the Central Bureau of Statistics in Buleleng Regency.